1990
DOI: 10.1002/art.1780331108
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and expression of the galactosyltransferase‐associated protein kinase gene in normal individuals and galactosylation‐defective rheumatoid arthritis patients

Abstract: We used restriction endonuclease digestion of leukocyte DNA to assess' the structural integrity of an N-acetylglucosamine pl+4 galactosyltransferase (GalTase)-associated (GTA) protein. kinase gene in rheumatoid arthritis (RA) patients. This analysis provides evidence that the gross structure of the GTA protein kinase gene locus remains intact in patients with defective galactosylation and that this gene locus is polymorphic both in normal individuals and in patients with RA, although no polymorphisms unique to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…GTase activity has been shown to be reduced in B lymphocytes of patients with rheumatoid arthritis (18), but this does not appear to be due to gross structural changes in either the GTase activator gene (19), the GTase gene itself, or to the presence of a soluble intracellular inhibitor (20).…”
Section: Introductionmentioning
confidence: 99%
“…GTase activity has been shown to be reduced in B lymphocytes of patients with rheumatoid arthritis (18), but this does not appear to be due to gross structural changes in either the GTase activator gene (19), the GTase gene itself, or to the presence of a soluble intracellular inhibitor (20).…”
Section: Introductionmentioning
confidence: 99%
“…The %G() was found to be higher in synovial fluid than in scrum, supporting the idea that agalactosyl IgG is produced in the joint in RA patients [10,11]. This change is associated with a down-regulation in B cell galactosyltransferase activity which in turn is controlled by the action of an associated protein kinasc [12]. Agalactosy!…”
Section: Introductionmentioning
confidence: 55%
“…In experiments using MRL mouse RA model, Axford et al reported a low Ga1T activity in peripheral lymphocytes [21]; and Jeddi et al a reduced expression of GaIT mRNA in spleen [22]. Taken together, the data suggest that it is more likely that the reduction in Ga1T activity in RA is due to an aberrant regulation of Ga1T mRNA expression through a variety of transcription factors and their phosphorylations by protein kinases such as GaIT-associated protein kinase [23]. The final proof must await the demonstration of a molecular mechanism that regulates the GaIT activity and its expression in RA patients.…”
Section: Discussionmentioning
confidence: 98%